(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Effective inventory management is pivotal for optimizing the financial health of small business enterprises (SBEs), particularly in resource-constrained regions like Cross River State, Nigeria. This study investigates how inventory management practices influence financial outcomes such as profitability, liquidity, and cost efficiency among SBEs in this region. Using a primary data collection approach, data were gathered via structured questionnaires from 150 SBE owners/managers across Calabar, Ikom, and Ogoja, selected through stratified random sampling. The study employs descriptive and inferential statistics, including regression analysis, to assess the relationship between inventory management techniques (e.g., Just-In-Time, Economic Order Quantity) and financial health indicators. Results reveal that SBEs adopting systematic inventory practices report a 15% higher profit margin and 20% improved cash flow compared to those with ad hoc approaches. Challenges such as inadequate technology, limited training, and supply chain disruptions were identified as barriers to effective inventory management. The study aligns with the Resource-Based View (RBV) theory, positing that inventory, as a strategic resource, enhances competitive advantage when efficiently managed. Recommendations include government-subsidized training programs, adoption of affordable inventory software, and strengthened local supply chains to bolster SBE financial stability. This research contributes to the limited literature on inventory management in Nigeria’s SBEs, offering actionable insights for policymakers and entrepreneurs aiming to enhance economic resilience in Cross River State.